2018
DOI: 10.23887/jppsi.v1i2.17214
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Guided Discovery Terhadap Keterampilan Proses Sains Siswa SMP Negeri 3 Sukasada

Abstract: Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan pengaruh model pembelajaran guided discovery terhadap keterampilan proses sains siswa. Populasi penelitian ini adalah seluruh siswa kelas VII SMP Negeri 3 Sukasada tahun ajaran 2017/2018. Pengambilan sampel dilakukan dengan teknik simple random sampling. Desain penelitian yang digunakan dalam penelitian ini adalah non-equivalent pretest-posttest control group desaign. Data keterampilan proses sains siswa dikumpulkan dengan menggunakan tes keterampi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 1 publication
0
5
0
6
Order By: Relevance
“…This practicum activity applies the scientific method, this shows that learning is not only in the form of delivering material but an experiment is needed to prove the concepts obtained (Kruit et al, 2018). The advantage of holding this practicum activity is to train students' scientific process skills and develop students' scientific attitudes (Fransiska et al, 2018;Inscription, 2018). With practicum activities, it is also very important because it can help students to improve their science process skills and students' critical thinking skills (Hamidah et al, 2014;Rahayu & Eliyarti, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This practicum activity applies the scientific method, this shows that learning is not only in the form of delivering material but an experiment is needed to prove the concepts obtained (Kruit et al, 2018). The advantage of holding this practicum activity is to train students' scientific process skills and develop students' scientific attitudes (Fransiska et al, 2018;Inscription, 2018). With practicum activities, it is also very important because it can help students to improve their science process skills and students' critical thinking skills (Hamidah et al, 2014;Rahayu & Eliyarti, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore it is concluded that there is a difference in the average post-test creative thinking skills between the experimental and control classes. Thus it can be said that there is a positive influence on the implementation of the guided discovery learning model on the creative thinking abilities of state high school students in West Lombok Regency [14].…”
Section: The Results Of Research At the State Senior High School In West Lombok Regencymentioning
confidence: 99%
“…Discovery Learning model pembelajaran berbasis teori kognitif yang menekankan peran guru dalam membentuk lingkungan belajar yang mendorong peserta didik secara aktif dan mandiri dalam membangun pengetahuannya (Jannah & Morina, 2020). Model pembelajaran Discovery Learning akan membantu mahasiswa dalam meningkatkan kemampuan berpikir kritisnya (Puspitasari & Nurhayati, 2019) serta memberikan kesempatan kepada siswa untuk menemukan sendiri pengetahuanya (Fransiska et al, 2018). Discovery dapat diartikan sebagai cara penyajian pembelajaran yang memberikan kesempatan kepada peserta didik untuk menemukan informasi dengan atau tanpa bantuan guru (Sirait, 2017).…”
Section: Pendahuluanunclassified